Characterization of friction angles for stability and deposition of granular material - Deganutti, Andrea M.; Tecca, Pia R.; Genevois, Rinaldo (Italian journal of engineering geology and environment, 2011)
The concept of friction angle as a measure of friction among bodies in static or dynamic conditions, is almost ubiquitous in Earth sciences. In spite of its importance, there is not a general agreement on its definition or standardization on the way to measure it. This study goes back to the fundamentals of friction among granular particles, presenting results from laboratory tests performed in order to measure the friction angles of particles of different shape, density and material, getting indications on the role of interparticle friction on the stability of a mass of granular material and on its depositional features. Several granular materials of different nature, natural and artificial, are studied in laboratory by means of a tilting flume. The aim of the performed tests is to measure the characteristic friction angles, both depositional (or repose) and stability limit (critical) taking into account the material characteristics: size, shape, density and roughness. The granular materials are heaped inside the flume which is then tilted until destabilization of the mass and the gradient of the new deposition surface is then measured by means of a lab-size laser scanner and a digital still camera; video shots of the motion of granules while sliding have been taken as well. The study shows that characteristic friction angles depend on size and shape of grains while when mixing granules of different size a sorting mechanism arises with less clear deposition angles. Although there are many other ways to measure friction angles (in particular by classical geotechnical apparatuses) the authors propose this way that is closer to the natural slope condition where granular mass flows originate.